THE FACTOR ANALYSIS THAT INFLUENCE THE STUDENT PURCHASE INTENTION IN SHOPEE E-COMMERCE - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2020)
The purpose of this research was to analyze the effect of Promotion, Website Quality and Trust on Purchase Intention in Shopee's e-commerce. The study employed purposive sampling with certain criteria and iteration formulas so that the number of samples obtained was 100 samples of Shopee e-commerce users from undergraduate students of The Economic Faculty of Pamulang University as respondents. By using Structural Equation Modeling with Partial Least Square Approach, the results indicated: (1) the promotion had positive and significant on purchase intention; (2) promotion had positive and significant on consumer’s trust; (3) The results showed that between variables there was no significant influence between consumer’s trust and purchase intention; (4 and 5) Website quality had a positive and significant influence on both purchase intention and consumer’s trust. However, (6 and 7) Both the promotion and website quality had no significant influence to purchase intention with consumer’s trust as intervening.